The Effect of Physical Evidence, Reliability, and Empathy on Customer Satisfaction at Setiabudi Salon - Rosmalina; Wulan Dayu; Dian Septiana Sari (Yayasan Multidimensi Kreatif, 2024)
This study aims to analyze the influence of Physical Evidence, Reliability, and Empathy on Customer Satisfaction at Setiabudi Salon. In this study, respondents were asked to provide responses regarding these three variables and their impact on their satisfaction levels as customers and on the population in this study was 67. The analysis methods used include descriptive and verifiable analysis, which include path analysis, multiple correlation analysis, determination coefficient, and hypothesis testing through t-test for partial testing and F-test for simultaneous testing. The population of this study consisted of 67 customers of Setiabudi Salon, with samples taken using saturated sampling techniques. The results of the analysis showed that Physical Evidence had a t-count value of 1.996, showing a positive and significant influence on customer satisfaction. Reliability recorded a t-count value of 3,170, which also shows a positive and significant influence. Meanwhile, Empathy produced a t-count value of 6,951, indicating a very significant influence on customer satisfaction. Simultaneously, the combination of these three factors showed a calculated F value of 122,985, which significantly affected customer satisfaction at Setiabudi Salon. This research emphasizes the importance of good management of Physical Evidence, Reliability, and Empathy to increase customer satisfaction, which will ultimately contribute to the loyalty and sustainability of the salon's business.